An improved method for extraction of nutraceutically important polyphenolics from Berberis jaeschkeana C.K. Schneid. fruits. (1st September 2017) - Belwal, Tarun; Giri, Lalit; Bhatt, Indra D.; Rawal, Ranbeer S.; Pande, Veena
Highlights: Design for polyphenolic antioxidants extraction from wild fruits was tested. Microwave assisted extraction was found superior as compared to UAE and ME. Under optimal MAE conditions 10 polyphenolic compounds at higher concentration was detected. The extraction design was found economically viable for industrial use. In vitro antioxidant and DNA damage protective activity indiactes its nutraceutical potential. Abstract: Berberis jaeschkeana fruits, source of nutraceutically important polyphenolics were investigated. A total of 32 experimental run were conducted under Plackett-Burman and central composite design. Microwave power, methanol and HCl concentration significantly (p < 0.05) affect extraction of polyphenols under linear, quadratic and interactive effect. The model showed good fitness with significant (p < 0.05) model F-value and a non-significant lack of fit. Under optimum microwave assisted extraction (MAE) condition the total phenolics, flavonoids, tannins and antioxidant activity were in closed context with predicted values. As compared to ultrasonic (UAE) and maceration extraction (ME), MAE showed significantly (p < 0.05) higher recovery of TP, TF and FRAP antioxidant activity. HPLC-DAD analysis detects a total of 10 polyphenolic compounds under MAE as compared to 9 under UAE and ME. Designing of MAE conditions showed promising results for polyphenolic antioxidants extraction as revealed by higher yield with lesser time and solvent consumption, which can contribute in green extraction technology and its application in nutraceutical industry.